FACTORS AFFECTING THE RISK OF DECUBITUS RISK IN LONG BARRELINE PATIENTS THAT ARE MAINTAINED IN BHAYANGKARA MAKASSAR HOSPITAL SURGERY ROOM - Nur Febrianti (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2019)
Introduction: Pressure sores (pressure sores) are sores that are localized to the skin and / or underlying tissues which are usually located on the part of the body where protrusions of bones result from pressure or a combination of pressure and friction. Method: The research design used was cross sectional design, namely analytic research design. The population was all old bed rest patients who were treated in the surgical treatment room of Bhayangkara Hospital Makassar, amounting to 38 people. Results: The results of the study were obtained from 38 respondents where there was no influence between gender and the risk of pressure sores in patients with long beds with a value of p = 0.122, there was an influence between age with the risk of pressure sores on patients with long beds with a value of p = 0.002, and there was an influence between the length of stay with the risk of pressure sores in patients with long bed rest with a value of p = 0,000 at Bhayangkara Hospital Makassar. Conclusion: There is no gender effect on the risk of pressure sores in long bed rest patients treated. There is an influence of age and length of stay on the risk of pressure sores in patients with long bed rest who were treated.